2019
DOI: 10.3934/mcrf.2019019
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control problem for exact synchronization of parabolic system

Abstract: This paper studies a kind of minimal time control problems related to the exact synchronization for a controlled linear system of parabolic equations. Each problem depends on two parameters: the bound of controls and the initial state. The purpose of such a problem is to find a control (from a constraint set) synchronizing components of the corresponding solution vector for the controlled system in the shortest time. In this paper, we build up a necessary and sufficient condition for the optimal time and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…The exact synchronization in the PDEs case was first studied for a coupled system of wave equations both for the higher-dimensional case in the framework of weak solutions in [15,16,19], and for the one-dimensional case in the framework of classical solutions in [11,17]. Recently, Pontryagin's maximum principle of optimal control problems for the exact synchronization of parabolic systems was studied in [34].…”
Section: Synchronization and Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact synchronization in the PDEs case was first studied for a coupled system of wave equations both for the higher-dimensional case in the framework of weak solutions in [15,16,19], and for the one-dimensional case in the framework of classical solutions in [11,17]. Recently, Pontryagin's maximum principle of optimal control problems for the exact synchronization of parabolic systems was studied in [34].…”
Section: Synchronization and Controlmentioning
confidence: 99%
“…There is a pair (A, B) satisfying (H 2 ). For example, In [34], we showed that the system (1.1) is exactly synchronizable at each time T if and only if either the following ( H 1 ) or ( H 2 ) is true: ( H 1 ) The pair (A, B) satisfies (1.6).…”
Section: Aim Motivation and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…In [7] and [8], were studied control problems on the source g and the flux q respectively, for parabolic variational inequalities of second kind. Other papers on the subject are [12,13,14,18,19,20,21,25,26,27]. Our interest is the convergence when α → ∞, which is related to [4,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…In most papers concerning minimal time control problems, people can provide necessary conditions for optimal controls, i.e., Pontryagin's maximum principle (see, for instance, [2], [11] and [14]). In some specific situations, people can also give characteristics for the optimal time, as well as the optimal control for a minimal time control problem (see, for instance, [12], [23] and [25]). We refer the reader to Remark 2.2 for a characteristic for the optimal control of the problem (T P ) τ M .…”
Section: Introductionmentioning
confidence: 99%